Promotion Strategy on Decisions on Using J&T Express Services, Pekanbaru - Erfa Okta Lussianda; Munawir Munawir (International Journal of Management Science and Information Technology, 2021)
In this study discusses the promotion of the Decision on the Use of J & T Express Services at PT Garuda Ekspress Nusantara in the city of Pekanbaru. The method used is using simple linear regression with the result Y = 5.878 + 0.925 X. From this equation it can be explained that kÎ±onstanta (Y = 5.878 + 0.925 X, from the equation can be explained that, the constant (a) is 5.878 stating that there is no the promotion of the use decision of 5.878. The regression coefficient of 0.925 states that each addition of one promotion unit it is predicted that the decision to use will increase by 0.925. This is because there is a relationship between promotion and decision to use services.The hypothesis testing is done by comparing the t statistic value with t table at alpha 5% and degree of freeom (df) = 96 - 2 = 94. So that the ttable value is 1,986. It is known that t count is 12,892 while t table is 1,986 (tcount 12,892 > ttable 1,986). t table, then t count > t table so the result is H0 is rejected, meaning the promotion has a role significant influence on Decision Use of J & T Express services at PT Garuda Ekspress Nusantara Pekanbaru.